The Effect of Benzyl Amino Purine (BAP) On Potato (Solanum tuberosum L.) Axillary Buds Micropropagation - Putri Anugrah Maulidya; Nurchayati, Yulita; Setiari, Nintya (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Potato (Solanum tuberosum L.) production in Indonesia increased by 4.21% in 2022 compared to the previous year, but this production is still low by international standards. This is caused by low quality and quantity of potato seeds which is sourced from tubers. It is necessary to modify the in vitro cultivation of potato seed sources by utilising seeds that are often wasted with the addition of cytokinins, such as Benzyl Amino Purine (BAP). The aim of this study was to determine the effect of BAP on potato axillary shoot explants sourced from seeds. The study was conducted using a Completely Randomized Design with one factor, namely BAP concentrations of 0, 1, 2 and 3 ppm with 3 replications. The results showed that there is an influence of BAP on the parameters of shoot growth percentage, leaf and root emergence time, plant height, number of shoots, roots, and leaves of potato axillary buds planlet. The 2 ppm BAP treatment tends to give the best response in increasing the number of shoots with an average of 4.33 shoots, making it effective for producing potato seedlings from axillary buds in vitro.